2018
DOI: 10.1097/mpa.0000000000001181
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Tumor Markers in Pancreatic Neuroendocrine Carcinoma and Their Values in Differentiation Between Pancreatic Neuroendocrine Carcinoma and Pancreatic Ductal Adenocarcinoma

Abstract: Objectives The levels of tumor markers in pancreatic neuroendocrine carcinoma (PNEC) are unknown, and imaging findings of PNEC and pancreatic ductal adenocarcinoma (PDAC) have overlaps. In this study, we show the tumor markers in PNEC and evaluate their values for distinguishing PNEC from PDAC. Methods Thirty-three cases of PDAC and 21 cases of PNEC were retrospectively evaluated. The demographic information and clinical data were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…CA19‐9 is a diagnostic tumor marker to differentiate between pancreatic adenocarcinoma and NETs 6,7 . Several studies of CA19‐9 in pancreatic NET patients have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CA19‐9 is a diagnostic tumor marker to differentiate between pancreatic adenocarcinoma and NETs 6,7 . Several studies of CA19‐9 in pancreatic NET patients have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…CA19‐9 is a diagnostic tumor marker to differentiate between pancreatic adenocarcinoma and NETs. 6 , 7 Several studies of CA19‐9 in pancreatic NET patients have been reported. Luo et al 3 reported that CA19‐9 > 16 U/ml was significantly associated with a higher proportion of patients at advanced stages and was an adverse prognostic factor for overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CA199 and CEA are sensitive and specific markers for PDAC diagnosis and prognosis. Abnormal CA199 and CEA levels have been found in Pan-NEC, while serum CA199, CEA, and AFP levels above the upper limit have been observed in 23.8%, 28.6% and 19.0% of PanNEC cases, respectively [69]. Abnormal CA199 and CA125 levels are more commonly found in PDAC than in PanNEC.…”
Section: Pathological Diagnosis and Serum Detectionmentioning
confidence: 97%